Divergent Neural Activity in the VLPO During Anesthesia and Sleep. Issue 2 (3rd December 2022) - Luo, Mengqiang; Fei, Xiang; Liu, Xiaotong; Jin, Zikang; Wang, Yingwei; Xu, Min
Abstract: The invention of general anesthesia (GA) represents a significant advance in modern clinical practices. However, the exact mechanisms of GA are not entirely understood. Because of the multitude of similarities between GA and sleep, one intriguing hypothesis is that anesthesia may engage the sleep‐wake regulation circuits. Here, using fiber photometry and micro‐endoscopic imaging of Ca 2+ signals at both population and single‐cell levels, it investigates how various anesthetics modulate the neural activity in the ventrolateral preoptic nucleus (vLPO), a brain region essential for the initiation of sleep. It is found that different anesthetics primarily induced suppression of neural activity and tended to recruit a similar group of vLPO neurons; however, each anesthetic caused comparable modulations of both wake‐active and sleep‐active neurons. These results demonstrate that anesthesia creates a different state of neural activity in the vLPO than during natural sleep, suggesting that anesthesia may not engage the same vLPO circuits for sleep generation. Abstract : It has long been thought that general anesthesia (GA) may use natural sleep regulation circuits because of similarities in the body and brain during GA and sleep. However, it is found that in the core sleep circuit, the neural activity induced by anesthetics is very different compared to natural sleep, suggesting that they are distinct brain states.